DNA barcoding reveals andropolymorphism in Aclerogamasus species (Acari: Parasitidae) MIROSŁAWA DABERT, AGATA BIGOŚ & WOJCIECH WITALIŃSKI (Poland) - Dabert, Mirosława; Bigoś, Agata; Witaliński, Wojciech (Zootaxa, 2011)
Andropolymorphism, defined as discontinuous morphological variability in males, can lead to taxonomic confusion when different male morphs are determined and described as separate species. This study addresses this issue in two occasionally sympatric mite species Aclerogamasus similis (Willmann, 1953) and A. holzmannae (Micherdziński, 1969) collected in Poland. The females of these two taxa are morphologically indistinguishable but males are quite different, and could be either separate species or one species with two male morphs. We address this question by performing molecular assays, testing variation in a fragment of the mtDNA COI gene and the D2 region of 28S rDNA. Molecular analysis of populations revealed very low variation in the studied gene fragments. All sequences of the D2 region of 28S rDNA (size 375 bp) were identical. Only two COI haplotypes were found, differing by two out of 644 nucleotide positions (0.3% K2P distance). The variant haplotype was found in one A. similis male, and probably represents intraspecific variability. The results strongly suggest that all studied females and males belong to only one species with dimorphic males. This finding confirms some earlier opinions on synonymy of both species. Therefore, Aclerogamasus holzmannae (Micherdziński, 1969) should be regarded as a junior synonym of Aclerogamasus similis (Willmann, 1953). As andropolymorphism has been rarely observed in gamasid mites, we briefly discuss its possible origins and consequences.